Using Facebook, Instagram, and Pinterest advertising campaigns to increase enrollment in newborn screening research - McInnis, Stephanie; Sobolewski, Jessica; Dass, Manisha; Gehtland, Lisa M.; Bailey, Donald B. (Frontiers in Communication, 2022)
Social media ad campaigns can be an efficient, cost-effective way to recruit for studies online, especially as the onset of the COVID-19 pandemic limited in-person recruitment. Early Check, a large ongoing study offering testing for a panel of conditions for all newborns in North Carolina, uses social media ad campaigns, along with direct mail, email, print materials in health care settings, and messages through patient portals to contact pregnant women and mothers with eligible newborns. All materials refer women to the online Early Check portal for consent and enrollment in the study. To evaluate social media options for outreach and recruitment, we ran two paid ad campaigns on Pinterest in May and July 2021 and compared performance to simultaneous Facebook and Instagram campaigns. Facebook and Instagram cost $136.53 per sign-up in May and July. Our first Pinterest campaign in May resulted in 206,416 impressions, 529 link clicks, and a cost per sign-up of $536.56. After adjusting the campaign to incorporate lessons learned about the platform, the second Pinterest campaign in July resulted in 225,286 impressions, 621 link clicks, and a cost per sign-up of $216.55. Others looking to implement social media ad campaigns for public health recruitment should note that ad costs have increased since 2020. However, social media ad campaigns on Facebook, Instagram, and Pinterest remain a cost-effective and convenient way to recruit participants for studies, especially when in-person efforts are not feasible. Ad campaign strategy should also be tailored to the specific platform. Facebook and Instagram ads should be run together in the same campaign to optimize the budget across both platforms and should run using an on-off schedule. Pinterest campaigns should run for a longer period to optimize continually for sign-ups over time.